Developing a Cooperative Research Agenda for Maine’s Commercial Fisheries - Alden, Robin; Mercer, Linda (Maine Policy Review, 2000)
This past year the Maine Department of Marine Resources sponsored a unique series of meetings involving fishermen, academic and government scientists, and fishery managers. The goal was to define a shared research agenda for Maine’s marine fisheries. Robin Alden and Linda Mercer summarize the results of these meetings. In doing so they address the question: “What do we need to know to properly manage Maine's major marine resources?” Alden and Mercer also conclude that the collaborative process these meetings helped to establish is one of the keys to the successful management of Maine’s marine resources.
Keywords: Maine; marine resources; commercial fisheries; fisheries research